Zircon U–Pb Dating of Tuff Layers in the Middle–Upper Triassic Strata of Successions and Sedimentation of Chang 7 Member in the Ordos Basin, China - Lu, Gang; Gou, Mingxing; Liu, Guanglin; Wang, Changcheng; Shi, Zhiqiang (Frontiers in Earth Science, 2022)
During the Late Triassic, the southern margin of the Ordos Basin was influenced the Indosinian Movement, in response to closure of the Paleo-Tethys Ocean and convergence between the Yangtze Plate and North China Plate. Thinly bedded tuff layers are exposed near the base of the Middle-Upper Triassic formations (Chang 8/7/6 Members) in the Ordos Basin. Tuff samples from drilling core (well An35) and outcrop (Motiangou section) samples in the Yanchang Formation were studied by detailed field work. Igneous zircon crystals were picked and analyzed by the instruments of cathodoluminescence and Laser Ablation Inductively Coupled Plasma Mass Spectro meter (LA-ICP-MS). The timing of volcanic activity was determined by means of high-precision zircon age. Combining tectonic setting and paleogeographic reconstruct, the ages of tuff layers indicates that volcanic activities were happened three peaks (241.6 ± 1.1 Ma, 240.2±1.1 Ma, 233.5 ± 1.2 Ma) from the top of Chang 8 Member to the Chang 7 Member. The results imply that the volcanic activities lasted from Ladinian to Carnian, as well as define the sedimentary duration of the Chang 7 Member with a deposition rate of 1.34 cm/ka.